Improved lifestyle is associated with improved depression, anxiety and well-being over time in UK healthcare professionals during the COVID-19 pandemic: insights from the CoPE-HCP cohort study - Ajay Gupta; Vikas Kapil; Mohammed Y Khanji; Sher May Ng; George Collett; Thomas Godec; Carmela Maniero; Imrana Siddiqui; Jaya Gupta (General Psychiatry, 2023)
Background One potential modifiable factor to improve the mental health of healthcare professionals (HCPs) during the pandemic is lifestyle.Aims This study aimed to assess whether an improved lifestyle during the pandemic is associated with improved mental health symptoms and mental well-being in HCPs over time.Methods This was a cohort study involving an online survey distributed at two separate time points during the pandemic (baseline (July–September 2020) and follow-up (December 2020–March 2021)) to HCPs working in primary or secondary care in the UK. Both surveys assessed for major depressive disorder (MDD) (Patient Health Questionnaire-9 (PHQ-9)), generalised anxiety disorder (GAD) (Generalised Anxiety Disorder-7 (GAD-7)), mental well-being (Short Warwick-Edinburgh Mental Well-being Score (SWEMWBS)) and self-reported lifestyle change (compared with the start of the pandemic) on multiple domains. Cumulative scores were calculated to estimate overall lifestyle change compared with that before the pandemic (at both baseline and follow-up). At each time point, separate logistic regression models were constructed to relate the lifestyle change score with the presence of MDD, GAD and low mental well-being. Linear regression models were also developed relating the change in lifestyle scores from baseline to follow-up to changes in PHQ-9, GAD-7 and SWEMWBS scores.Results 613 HCPs completed both baseline assessment and follow-up assessment. Consistent significant cross-sectional associations between increased lifestyle change scores and a reduced risk of MDD, GAD and low mental well-being were observed at both baseline and follow-up. Over the study period, a whole unit increase in the change in novel scores (ie, improved overall lifestyle) over 4 months was inversely associated with changes in PHQ-9 (adjusted coefficient: −0.51, 95% confidence interval (CI): −0.73 to −0.30, p<0.001) and GAD-7 scores (adjusted coefficient: −0.32, 95% CI: −0.53 to −0.10, p=0.004) and positively associated with the change in SWEMWBS scores (adjusted coefficient: 0.37, 95% CI: 0.18 to 0.55, p<0.001).Conclusions Improved lifestyle over time is associated with improved mental health and mental well-being in HCPs during the pandemic. Improving lifestyle could be a recommended intervention for HCPs to help mitigate the mental health impact during the current and future pandemics.Trial registration number NCT04433260.